Consolidation and swell characteristics of dispersive soils stabilized with lime and natural zeolite - Savaş Hasan (Science and Engineering of Composite Materials, 2016)
Many engineering structures such as dam embankments, road way embankments have suffered serious erosion problems and have failed due to the presence of the dispersive soils. Different additives are used to control the dispersivity properties of these soils. In this study, the effects of lime and natural zeolite on the consolidation and swell characteristics of dispersive clay soils were investigated. For this purpose, identification and compaction tests were carried out on the soil samples. Dispersivity, swell and consolidation tests were performed on the specimens prepared by standard Proctor energy and constant lime content levels (2%, as a percentage of dry weight of the soil), the percentage (0%, 1%, 3%, 6%, 10%, 15% and 20%) of a mixture of natural zeolite additives. As a result of this study, it is shown that the dispersive soils can sufficiently be treated using lime and natural zeolite. From the test results, 2% lime and 3% natural zeolite was the most effective stabilizer in decreasing swell and compressibility potential of dispersive soils.